Malnutrition and lung cavity formation in pulmonary tuberculosis patients - Christi Giovani Anggasta Hanafi; Fariz Nurwidya; Wiji Lestari; Heidy Agustin (World Nutrition Journal, 2023)
Background: Tuberculosis (TB) is an infectious disease and still major public health threat globally, also one of the leading causes of death worldwide. One of the characteristics found in pulmonary TB patient is lung cavity on their chest radiograph. This is related to many aspects, including slower conversion of sputum cultures, treatment failure and relapse, drug resistance, higher bacillary load, even higher infection transmission rates. Some studies before had found that the lung cavity is affected by many factors, such as elder age, sex, diabetes mellitus, and malnutrition. Meanwhile, malnutrition itself in pulmonary TB patients is found to be related to each other, this article review how malnutrition affects the formation of lung cavity in pulmonary TB patients. Objective: To observe the relationship between malnutrition and lung cavity formation in pulmonary tuberculosis patients. Method: In this paper, we provide a literature review. The method to achieve the objective consists of using literature exploration, which was conducted from October 2022-February 2023 by searching the relevant studies from several databases. Results: Cavity formation in pulmonary TB patients is a complex mechanism from many factors contributing, including the immune system of the host. Studies show that malnutrition in pulmonary TB patients plays important role linked to lung cavity formation since malnutrition affects both innate and cellular immune response in host. Conclusion: Malnutrition is more predominating in pulmonary TB patients and is related to incidence of lung cavity in pulmonary TB patients, therefore plays role in the severity of the disease in pulmonary TB.